Mechanism Study on the Main Causes of Forming Low-Contrast Oil Reservoirs in the Doseo Basin of Chad - CHEN Liangyu; JU Xiaolong; HUANG Liang; LI Yonggui; CHEN Zhi; FU Jianwei (Cejing jishu, 2025)
The identification of low-contrast reservoirs represents one of the major challenges currently facing the petroleum industry. The genesis of low-contrast reservoirs in the Kapok area of the Doseo basin in Chad is diverse and the oil-water relationship is complex, and the use of conventional petrophysical evaluation techniques often leads to difficulties in oil-water identification. Therefore, there is an urgent need to carry out reservoir characteristics and genesis mechanism studies in the Doseo basin. This paper takes the Kapok area in the Doseo basin of Chad as the object of study, and integrates the geological background of the area and well logging data to deepen the geological understanding of the low-resistivity oil reservoirs on the basis of the study of petrophysical genesis. The evaluation of the pore structure characteristics of reservoir rocks using NMR method is characterised by significant advantages, and by measuring the relaxation time of hydrogen nuclei in the rocks to reveal the reservoir reservoir storage space characteristics and fluid mobility. For the muddy sandstone reservoir with high content of immonium mixture, the water saturation of the original formation was determined based on the Waxman-Smits equation with full consideration of the effect of additional electrical conductivity of cations. As verified by the oil test results, the model calculated saturation is in good agreement with the water saturation and bound water saturation of the test formation. Combined with the formation water resistivity experiment, the core resistivity of the test oil formation decreases with increasing salinity. Clarified that high bound water saturation, additional electrical conductivity of clay and difference in formation water salinity are the main causes for the formation of low-contrast oil layers, preliminary formation of the identification and evaluation system for the genesis of low-resistivity reservoirs in Doseo basin of Chad.